General practitioners (San Juan, Metro Manila) their actual limitation in treating patients with orthodontic problems - Borja, Sylvia
Due to the wide range of services offered by the general dental practitioner, questions have risen as to their actual limitations in treating orthodontic problems. What type to cases do they handle? When do they refer? What factors do they consider in case selection? There has been some confusion in that there has been no clear demarcation of cases which may be handled within the framework of the general practitioner. Results show that a factor considered in case selection is severity of the case, and familiarity of the case to the general practitioner. Most G.P.s also use appliances previously learned in school which are for simple cases. Therefore, most general practitioners (in San Juan, Metro Manila) do not handle cases which they feel are beyond the framework of their basic orthodontic knowledge. The general practitioner of the future should be able to select intelligently those patients whom he can handle orthodontically within the framework of the general practitioner, and those who would be better handled on a referral basis.